Kiai as the Activator for Accelerating the Implementation of Child-Friendly Pesantren Based on the Local Wisdom - Zaki Mubarok; Zakiyah Zakiyah; Ani Khofifah (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
This service is done to accelerate the implementation of child-friendly Islamic boarding schools in Tegal Regency which has come to the piloting stage or as prospective models. The service method is Participatory Action Research (PAR) whose process aims at learning in overcoming problems and meeting the practical needs of the pesantren by identifying problems, evaluating and exploring potential in accelerating the implementation of child-friendly pesantren. The output of the community service is that the Kiai and the management of the pesantren understand the laws and regulations regarding child protection and various types of child abuse that must be avoided, propose a Regent's Regulation as a follow-up to the Regional Regulation on Facilitation of Pesantren Development, strengthen the governance of pesantren for the creation of child-friendly pesantren, cooperate with various related parties for socialization and counseling related to child-friendly pesantren, and design a pesantren curriculum with standard student behavior.